Rekonstruksi Makna Riba dalam Al-Qur’an dan Tantangannya dalam Sistem Ekonomi Modern - Surinten; Abdul Syukkur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
Riba is a fundamental concept in Islamic muamalah that is explicitly prohibited in the Qur’an, yet it continues to generate interpretive debates within the context of modern economic practices. This study aims to reconstruct the meaning of riba in the Qur’an and to analyze the challenges of its interpretation in contemporary economic systems. This research employs a qualitative method using a library research approach with thematic (maudhu’i) tafsir. The study focuses on Qur’anic verses related to riba, particularly in Surah Al-Baqarah, Ali Imran, An-Nisa, and Ar-Rum, as interpreted by classical and contemporary exegetes. The findings indicate that riba in the Qur’an is not merely understood as an additional charge in debt transactions, but rather as an exploitative economic practice that contradicts the principles of justice and social welfare. This reconstruction highlights that the prohibition of riba is closely related to ethical and socio-economic dimensions, not solely formalistic legal aspects. Therefore, a contextual understanding of riba is necessary to address the complexities of modern economic systems.